Investigating TSPO levels in occupation-related posttraumatic stress disorder - Sarah E. Watling; Talwinder Gill; Erin V. Gaudette; J. Don Richardson; Tina McCluskey; Junchao Tong; Jeffrey H. Meyer; Jerry Warsh; Rakesh Jetly; Michael G. Hutchison; Shawn G. Rhind; Sylvain Houle; et al. (Scientific Reports, 2023)
Abstract Microglia are immune brain cells implicated in stress-related mental illnesses including posttraumatic stress disorder (PTSD). Their role in the pathophysiology of PTSD, and on neurobiological systems that regulate stress, is not completely understood. We tested the hypothesis that microglia activation, in fronto-limbic brain regions involved in PTSD, would be elevated in participants with occupation-related PTSD. We also explored the relationship between cortisol and microglia activation. Twenty participants with PTSD and 23 healthy controls (HC) completed positron emission tomography (PET) scanning of the 18-kDa translocator protein (TSPO), a putative biomarker of microglia activation using the probe [18F]FEPPA, and blood samples for measurement of cortisol. [18F]FEPPA VT was non-significantly elevated (6.5–30%) in fronto-limbic regions in PTSD participants. [18F]FEPPA VT was significantly higher in PTSD participants reporting frequent cannabis use compared to PTSD non-users (44%, p = 0.047). Male participants with PTSD (21%, p = 0.094) and a history of early childhood trauma (33%, p = 0.116) had non-significantly higher [18F]FEPPA VT. Average fronto-limbic [18F]FEPPA VT was positively related to cortisol (r = 0.530, p = 0.028) in the PTSD group only. Although we did not find a significant abnormality in TSPO binding in PTSD, findings suggest microglial activation might have occurred in a subgroup who reported frequent cannabis use. The relationship between cortisol and TSPO binding suggests a potential link between hypothalamic–pituitary–adrenal-axis dysregulation and central immune response to trauma which warrants further study.